Optimasi Penjadwalan Mata Pelajaran Berbasis Kurikulum Merdeka Menggunakan Integer Linear Programming - Permana, Rendy Candra; Hanum, Farida; Bakhtiar, Toni; Supriyo, Prapto Tri (Universitas Negeri Gorontalo, 2025)
Scheduling subjects in secondary schools implementing the kurikulum merdeka presents a complex challenge. Kurikulum merdeka demands a high degree of flexibility, fulfillment of individual learning needs, and integration between mandatory and elective subjects. The complexity increases due to time constraints, uneven distribution of teaching loads, limited classroom availability, and potential schedule conflicts between teachers and students. The manual approach, which is still commonly used, is often inefficient, time-consuming, and results in suboptimal schedules. To address these challenges, this study proposes an automated scheduling model based on Integer Linear Programming (ILP), implemented using LINGO 19.0 software. The model considers various real-world constraints, such as the maximum number of study hours per day, designated days for mandatory and elective subjects, the requirement for two consecutive periods per subject, and teacher availability. A case study was conducted for Grade XI at SMAN 58 Jakarta, involving 9 classes, 32 teachers, and 18 subjects (9 mandatory and 9 elective). The experimental results show that the model can produce efficient, conflict-free schedules, accelerate the scheduling process, and support equitable teacher workload distribution.